THE IMPORTANCE OF VALUES IN ENHANCING CIVIL LITERACY IN STUDENTS (Archive of Conferences, 2021)
the article covers the importance of values in increasing the civil literacy of students and isdedicated to enlightening the values of freedom, peace, justice, social equality, enlightenment, truth, goodness,beauty, material and spiritual riches, traditions, customs and others.